Dietary creatine improves the growth performance, antioxidant capacity and energy metabolism of common carp (Cyprinus carpio) by activating glucose metabolism and the Nrf2-Keap1 pathway - Meiqi Xing; Xinchi Shang; Longwu Geng; Haijun Wei; Xinghua Che; Xiaodan Shi; Zhengwei Li; Hailong He; Wei Xu (Aquaculture Reports)
Creatine (Cr) is used as a feed additive to improve energy metabolism, regulate lipid metabolism, and increase antioxidant activity in and promote the growth of fish. However, the potential mechanism by which creatine regulates hepatic energy metabolism and antioxidant capacity in carp is not clear. In this study, 180 carp (63.86 ± 1.87 g) were randomly divided into three treatment groups and fed diets containing 0, 0.5 or 2.5 g/kg creatine for 6 weeks. The effects of creatine on common carp were evaluated through histological observations, biochemical analyses, and quantitative real-time polymerase chain reaction (qRT-PCR). The growth data revealed that the addition of 0.5 g/kg creatine significantly increased the weight gain rate (WGR), specific growth rate (SGR), feed efficiency ratio (FER), and protein efficiency ratio (PER) of common carp (P < 0.05). Histological observations indicated that the addition of 0.5 g/kg creatine promoted common carp intestinal development. On the other hand, the addition of 0.5 g/kg creatine significantly reduced the levels of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), γ-glutamyl transferase (GGT), total cholesterol (TC), and triglycerides (TG) (P < 0.05), increasing their resistance to liver injury and improving lipid metabolism. The addition of 0.5 g/kg and 2.5 g/kg creatine significantly increased the activity of hepatic ATPase (P < 0.05) and improved hepatic energy metabolism by significantly increasing the mRNA expression levels of phosphoenolpyruvate carboxykinase 2 (PCK2), glycogen synthase 2 (GYS2), and pyruvate kinase (PK). In addition, the addition of 0.5 g/kg creatine activated the Nrf2-Keap1 pathway; significantly increased the activities of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX); increased the total antioxidant capacity (T-AOC); and decreased the content of malondialdehyde (MDA) (P < 0.05), which improved antioxidant capacity. The results of this study indicate that supplementation with 0.5 g/kg creatine is optimal. This study provides a theoretical basis for the application of creatine as a valuable feed additive in aquaculture.